REFLEXUL SENSITIVITĂŢII SISTEMULUI CARSTIC ÎN MORFOLOGIA CARSTICĂ STUDIU DE CAZ: COMPLEXUL CARSTIC DAMIŞ – PONORAŞ (MUNŢII PĂDUREA CRAIULUI) (PANGEEA, 2025)
The morphological response of karst system’s sensitivity. The karst complexum of Damiş – Ponoraş (Pădurea Craiului Mountains) – a case study The karst complexum of Damiş – Ponoraş is a typical karst region in the Pădurea Craiului Mountains. Being settled between the valeys of Crişul Repede (north), and two of its afluents: Brătcuţa (east) and Mişid (west), this exceptional karst region is caracterized by a mature phase of karst evolution, in which there can be find many correlations between the exokarstic and the endokarstic subsistems. Therefore, we tried to localize this interrelations, based on our researches in the field, but in the same time having a great help from studies of researchers, such as T. Rusu, P. Cocean, I. Orăşeanu or B.P. Onac, but also from speleological groups. After we have analized the control factors of the geosystem, we tried to identify that exokarstic and endokarstic responses of karst system’s sensitivity, that are making this karst area so attractive for tourists and scientifical researchers, as well.